2023
DOI: 10.1002/chir.23604
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental symmetry origins in the chiral interactions of optical vortices

Abstract: Recently, a variety of mechanisms have been discovered that extend the range of optical techniques for identifying and characterizing molecular chirality, beyond those associated with optical polarization. It is now evident that beams of light with a twisted wavefront, known as optical vortices, can also interact with chiral matter with a specificity determined by relative handedness. Exploring this chiral sensitivity of vortex light in its interactions with matter requires careful consideration of the symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…Light field with orbital angular momentum (OAM) is also known as vortex beam which has been well applied in optical tweezers, [12] communication, [13] manufacturing, [14] etc. [15,16] The helical wavefront also gives vortex beam a chiral degree of freedom and its handedness is determined by the sign of the OAM munber l. [17][18][19] Interestingly, recent theoretical and experimental studies have demonstrated that the interaction between vortex beam and chiral matters depends on the sign of l. [20][21][22][23][24][25][26][27][28][29][30] This suggests that photonic OAM can provide another promising approach to investigate chiral physics. The giant helical dichroism (HD) has been achieved for a single helix, [25,29] planar-chiral nanostructure, [26] twisted stereometamaterial, [27] and chiral oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…Light field with orbital angular momentum (OAM) is also known as vortex beam which has been well applied in optical tweezers, [12] communication, [13] manufacturing, [14] etc. [15,16] The helical wavefront also gives vortex beam a chiral degree of freedom and its handedness is determined by the sign of the OAM munber l. [17][18][19] Interestingly, recent theoretical and experimental studies have demonstrated that the interaction between vortex beam and chiral matters depends on the sign of l. [20][21][22][23][24][25][26][27][28][29][30] This suggests that photonic OAM can provide another promising approach to investigate chiral physics. The giant helical dichroism (HD) has been achieved for a single helix, [25,29] planar-chiral nanostructure, [26] twisted stereometamaterial, [27] and chiral oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…Chirality is a universal symmetry property of matter and waves that is important in biology, medicine, physics, , and materials science . In optics, chiral effects usually involve chiral light, characterized by helical waves carrying angular momentum. The helical phase structure or field pattern rotation produces orbital angular momentum (OAM), while the rotation of the light polarization vector introduces spin angular momentum (SAM) . Analogies between electron and optical spin effects have recently led to the investigation of novel chiral states of light, such as photonic skyrmions. , Similar to their magnetic skyrmion counterparts, these spin-optical textures are topologically protected against external perturbations.…”
mentioning
confidence: 99%